Distribution of aid and outreach as an effort to develop snack food MSME in Galengdowo village, Wonosalam, Jombang - Lestari, Danik Dwi; Panggayuh, Danang Andrian Fajar; Setiawan, Risqi Firdaus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The development of micro, small and medium enterprises (MSMEs) in the snack food sector is an important strategy to improve the local economy and empower rural communities. This research explores the effectiveness of aid distribution and outreach as an effort to develop snack food MSMEs in Galengdowo Village, Wonosalam, Jombang. Using a qualitative approach, a case study was conducted to examine the impact of capital assistance, training, and the introduction of digital technology on increasing production capacity, product quality, and market access for MSMEs. The study results show that the assistance provided has had a significant positive impact, including improvements in business management, online marketing, and development of partnership networks. Socialization regarding marketplaces and digital marketing strategies has also proven effective in increasing product visibility and creating added value for MSMEs. However, challenges such as limited information technology infrastructure remain obstacles that need to be overscome to support the sustainable growth of MSMEs in the future.